FAKTOR KEJADIAN ANEMIA PADA REMAJA PUTRI DI MTSN TALAWI KOTA SAWAHLUNTO - Novi Wulan Sari (Menara Ilmu, 2019)
Anemia occurs where blood levels of Hb <12 mg / dl. In Indonesia the prevalence of anemia 57,1% was suffered by young women aged 10-18 years. In Sawahlunto from 14 schools, Islamic Junior High School Talawi was the highest anemia. 33 or 61.1% Hb levels <10 gr%, 21 (38.9%) Hb levels 10-11.9 gr%, and 0 (0%) Hb level> = 12gr%. This research aimed to determine Some Factors Related to Anemia in Teenagers in Islamic Junior High School Talawi, Sawahlunto. The type of this research was analytic survey with cross sectional design. It was conducted on January, 2019 in Islamic Junior High School Talawi, Sawahlunto. The populations were all female teenager students in Islamic Junior High School Talawi, Sawahlunto. Then, by using Quota Sampling techniques, 62 students were chosen as the samples. The data were analyzed by univariate and bivariate with Chi-square test (significance degree of 95% (p <0.05)). The results of this research showed that 33 or 53.2% of the respondents had lack of knowledge about anemia. Then, 39 of them (62.9%) consumed inadequate food intake. Then, 39 or 62.9% of the respondents did not consume added blood tablets. After that, 38 of them (61 , 3%) suffered from anemia. Moreover, there was relationship between knowledge (p= 0.000, OR = 7.364), food intake (p= 0,000, OR = 12.95) and tablet consumption (P= 0.001, OR = 6,250) with anemia. In short, it was concluded that there should be an effort to carry out activities related to health education about the dangers of anemia and how to prevent it so that the incidence of anemia in young women can be overcome. Especially teenagers, health workers, and schools together working together to reduce the incidence of anemia at MTSN Talawi, Sawahlunto City. Keywords : Knowledge, Food Intake, Consumption of Blood Add Tablets, , Anemia